PENGARUH LEVERAGE, FIRM SIZE, FIRM AGE DAN SALES GROWTH TERHADAP KINERJA KEUANGAN - Alvina Maria Krisanthi Cahyana, Rousilita Suhendah (Jurnal Paradigma Akuntansi, 2020)
This research aims to obtain empirical evidence about the effect of leverage, firm size, firm age and sales growth on financial performance. The population data in this research are manufacturing companies listed on Indonesia Stock Exchange (BEI) for a period of 2016-2018 obtained from www.idx.co.id. This research was conducted with a total sample of 70 manufacturing companies from a total population of 163 manufacturing companies. The research data processing uses Eviews software version 10.0. The results of this research showed that firm age has a positive and significant effect on financial performance, sales growth has a negative and significant effect on financial performance, but leverage and firm size has no impact on financial performance.